Comparison of Fecal Inflammatory Markers in Crohn's Disease. Issue 5 (May 2016) - Wright, Emily K.; Kamm, Michael A.; De Cruz, Peter; Hamilton, Amy L.; Ritchie, Kathryn J.; Keenan, Jacqueline I.; Leach, Steven; Burgess, Laura; Aitchison, Alan; Gorelik, Alexandra; Liew, Danny; Day, Andrew S.; et al.
Abstract : Background: Fecal biomarkers are used increasingly to monitor Crohn's disease (CD). However, the relative accuracy of different markers in identifying inflammation has been poorly evaluated. We evaluated fecal calprotectin (FC), lactoferrin (FL), and S100A12 (FS) using endoscopic validation in a prospective study of the progression of CD after intestinal resection. Methods: Data were collected from 135 participants in a prospective, randomized, controlled trial aimed at preventing postoperative CD recurrence. Three hundred nineteen stool samples were tested for FC, FL, and FS preoperatively and 6, 12, and 18 months after resection. Colonoscopy was performed at 6 and/or 18 months. Endoscopic recurrence was assessed blindly using the Rutgeerts score. C-reactive protein (CRP) and Crohn's Disease Activity Index (CDAI) were assessed. Results: FC, FL, and FS concentrations were elevated preoperatively (median: 1347, 40.9, and 8.4 μg/g, respectively). At 6 months postoperatively, marker concentrations decreased (166, 3.0, 0.9 μg/g) and were higher in recurrent disease than remission (275 versus 72 μg/g, P < 0.001; 5.7 versus 1.6 μg/g, P = 0.007; 2.0 versus 0.8 μg/g, P = 0.188). FC > 135 μg/g, FL > 3.4 μg/g, and FS > 10.5 μg/g indicated endoscopic recurrence (score ≥ i2) with a sensitivity, specificity, and negative predictive value (NPV) of 0.87, 0.66, and 91%; 0.70, 0.68, and 81%; 0.91, 0.12, and 71%, respectively. FC and FL correlated significantly with the presence and severity of endoscopic recurrence, whereas FS, CRP and CDAI did not. Conclusions: FC was the optimal fecal marker for monitoring disease activity in postoperative CD and was superior to CRP and CDAI. FL offered modest sensitivity for detecting recurrent disease, whereas S100A12 was sensitive but had low specificity and NPV. Abstract : Article first published online 28 January 2016.